The Serbo-Croatian Accent in the Pronunciation of English Seen in the Light of the Monitor Theory - Josipović, Višnja (Array, 1989)
This paper presents the results of a research in which some basis notions of the Monitor Theory are applied to the study of a Croatian accent in the pronunciation of English. The author elaborates a methodology for expressing numerically the degree of monitoring in the use of a foreign language and establishes a correlation between the degree of monitoring and the success of pronunciation in particular phonostylistic registers. The greater the degree of monitoring, the greater is the difference in the quality of pronunciation of English between the formal and informal style, in favour of the former.Thus the subjects who showed a greater degree of monitoring pronounced English better when reading a text than they did in informal conversation. The subjects who were less inclined to monitoring pronounced much better in the informal style.